On the Evolution of Corruption Patterns in the Post-Communist Countries - Andrzej Cieslik; Lukasz Goczek (Institute of Economic Research (IER), 2015)
In this paper, we study the evolution of corruption patterns in 27 post-communist countries during the period 1996-2012 using the Control of Corruption Index and the corruption category Markov transition probability matrix. This method allows us to generate the long-run distribution of corruption among the post-communist countries. Our empirical findings suggest that corruption in the post-communist countries is a very persistent phenomenon that does not change much over time. Several theoretical explanations for such a result are provided.
Keywords: D73; P21; P37; 330; corruption; Markov transition probability matrix; post-communist countries